2016
DOI: 10.1111/gtc.12345
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance analysis of the conformational state of cancer mutant of fibroblast growth factor receptor 1 tyrosine kinase domain

Abstract: Tyrosine kinases are key enzymes that play critical roles in growth signaling, the abnormal activation of which is associated with various human cancers. Activation of tyrosine kinases is mediated by tyrosine phosphorylation in the activation‐loop, which transforms the catalytic domain to the active state conformation. Cancer mutations are supposed to transform the conformation of the catalytic domain into the active‐form independent of the phosphorylation state of the activation‐loop. Here, we report structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Nuclear magnetic resonance analysis of the effect of the gatekeeper mutation on the conformational state of the P-loop region of FGFR1 Upon activation by phosphorylation, FGFR1 shows substantial structural change around the nucleotidebinding loop (P-loop), the activation loop and the C- helix (Chen et al 2007). Our NMR analysis showed that the gatekeeper mutation of FGFR1, V561M, showed a locally activated structure around the P-loop (Kobashigawa et al 2016). The crystal structure of the complex formed between FGFR1 and PD173074 showed that the tert-butyl group interacted with the P-loop (Mohammadi et al 1998).…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…Nuclear magnetic resonance analysis of the effect of the gatekeeper mutation on the conformational state of the P-loop region of FGFR1 Upon activation by phosphorylation, FGFR1 shows substantial structural change around the nucleotidebinding loop (P-loop), the activation loop and the C- helix (Chen et al 2007). Our NMR analysis showed that the gatekeeper mutation of FGFR1, V561M, showed a locally activated structure around the P-loop (Kobashigawa et al 2016). The crystal structure of the complex formed between FGFR1 and PD173074 showed that the tert-butyl group interacted with the P-loop (Mohammadi et al 1998).…”
Section: Resultsmentioning
confidence: 76%
“…We introduced an R627E mutation, which greatly improved the solubility and stability without substantially perturbing the structure of the FGFR1 kinase domain (Kobashigawa et al . , ). Figure shows the overlay of the NMR spectra of the Met 13 CH 3 ‐labeled FGFR1 gatekeeper mutants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations